Fetal growth in low-risk Indian population at a tertiary centre and its comparison with INTERGROWTH-21 standards: a prospective cohort study - Ravi, Anoosha K.; Agarwal, Krishna; Ramji, Siddarth; Vishnubhatla, Sreenivas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of this study was to compare the fetal growth pattern in low risk Indian population with the INTERGROWTH-21 standards. Methods: Low risk women were enrolled at 10 to 20 weeks of gestation and followed up until delivery. An experienced operator performed abdominal ultrasound every 5±1 week and measured biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC) and femur length (FL) of the fetus. Newborn anthropometric measurements were taken within 12 hours of childbirth. Results: A total of 126 healthy women, enrolled at mean gestation of 16.8±1.6 weeks, completed the follow up until delivery. None of the participants developed any major obstetric or medical morbidity. The study subjects showed lower mean z scores for BPD (-0.7±1.3), HC (-0.4±1.3) and AC (-0.4±1.3) but a higher mean z-score for FL (0.3±1.7) as compared to INTERGROWTH-21 standards. From 1st through 5th visit, the z scores for BPD and HC improved whereas declined for AC and FL. Conclusions: The fetal growth in non-affluent healthy Indian women had a lower fetal growth compared to INTERGROWTH-21 standards.